Tobias Norlind och musiken i Sverige under Vasatiden - Hedell, Kia (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2006)
Tobias Norlind and music in Sweden during the Vasa period Tobias Norlind (1879–1947), generally described as a pioneer of Swedish musicology, is noted for his research into the history of early music in Sweden. This article discusses aspects of Norlind’s contribution to our knowledge of music life during the Vasa period (1521–1611), focusing on two of his books: Kungliga Hovkapellets historia 1526–1926 (The history of the Royal court chapel 1526–1926), co-authored with Emil Trobäck (1926) and Från Tyska kyrkans glansdagar (From the splendid days of the German church), volumes 1 and 2 (1944). These works, while retaining much of their importance for our understanding of music in the Vasa period, nevertheless present problems. A major concern is the basic archival research on which these books are based. How much was Norlind’s own work? In the article, I show that it was in fact Emil Trobäck who was mainly responsible for collecting facts about musicians and music-making at the Vasa courts, and that in Från Tyska kyrkans glansdagar, Norlind then re-used this data, generally without explicit acknowledgement. This information has relevance for future research on Vasa music life. It is also significant for our understanding of Tobias Norlind as a researcher of primary sources and a specialist in the history of 16th and 17th-century Swedish music.